Molecular pathogenesis of infections caused by Moraxella catarrhalis in children (Swiss Medical Weekly, 2012)
Moraxella catarrhalis (M. catarrhalis) is a human-restricted commensal of the normal bacterial flora in the upper respiratory tract of children, and – during the previous two decades – has been recognised as a true human pathogen. M. catarrhalis is the third most common pathogen causing acute otitis media in children, which is the most common reason to visit a paediatrician during childhood. Acute otitis media thus causes a high clinical and economical burden. With the introduction of the conjugate pneumococcal vaccines the microbiomic pattern in the nasopharyngeal flora of children has changed, and the frequency of isolation of M. catarrhalis has increased. Compared to adults, children are more often colonised with M. catarrhalis. Over the last three decades there has been a dramatic increase in the acquisition of β-lactam resistance in M. catarrhalis. Today 95–100% of clinically isolated M. catarrhalis produce β-lactamase. It is thus desirable to reduce the burden of M. catarrhalis disease by developing a vaccine. There are several potential vaccine antigen candidates in different stages of development, but none of them has entered clinical trials at the present time.